New records of Pluteus Fr. (Basidiomycetes, Agaricales, Plutaceae) in Mexico - Rodríguez, Olivia; Guzmán-Dávalos, Laura (Instituto de Ecología, A.C., 2007)
Three species of genus Pluteus Fr., new to the Mexican mycobiota are reported: Pluteus amphicystis, P. martinicensis and P. oligocystis. The first two species belong to section Pluteus and the last one to section Celluloderma. Besides, P. atromarginatus and P. salicinus, both belonging to section Pluteus, are described; previously they were only known from the states of Jalisco and Hidalgo, respectively. Pluteus atromarginatus is reported for the first time from Veracruz.